Efeito da concentração de Leifsonia xyli subsp. xyli na termoterapia e no peso de colmos em três variedades de cana-de-açúcar - Andreato, Caroline (2020)
Ratoon stunt disease (Leifsonia xyli subsp. xyli), is currently considered the main disease of sugarcane in all major producing countries. Because propagating materials is the sole source of primary inoculum, the use of clean seedcanes is paramount for the success of disease control, making laboratory diagnosis mandatory to verify the phytosanitary conditions of the propagating materials. The sorological diagnostic technique is employed all over the world for the routine test by almost all sugarcane producing countries. Other recommendation to RSD control includes heat-treatment of seedpieces. In Brazil, the thermotherapys adopted are 52°C/30min and 50°C/2h, whereas only the second one is employed in other countries. Each combination has different characteristics, 52°C/30min showed no deleterious effect on budding but less elimination of Lxx, while the opposite happened in 50°C/2h. However, the consequences of this failure on sugarcane production is unknown. Thus the objective of this work was to understand the effect of variety on the result of thermotherapy and to compare the Dot Blot and PCR methods for detection and control of the RSD. To that, 400 plants of each of the varieties RB867515, RB92579 and RB966928 were used, cultivated according to a randomized block design with five replications and four treatment conditions (two thermotherapy conditions, infected control and uninfected control). The harvesting was done at nine monhs of age in the field and the plants were evaluated by Dot Blot and PCR methods for the detection of Lxx. Data of this investigation showed: a) the varieties respond differently to the thermotherapy conditions; b) the initial concentration of Lxx is of paramount importance for efficient thermal control; c) the short heat treatment was efficient when the Lxx concentration was low in the varieties RB92579 and RB867515; d) the Dot Blot and PCR techniques showed 99% correspondence, despite the greater detection efficiency of the PCR and e) RSD did not influence the weight of plant cane of varieties RB966928, RB867515 and RB92579, in cane plant of 9 months in the field.